SMART HEALTHCARE SYSTEM DESIGN: Security and Privacy Aspects - S. K. Hafizul Islam, editor; Samanta, Debabrata, editor (Hoboken : John Wiley and Sons Inc, 2021)
Includes bibliographical and references